ACCLIMATIZATION OF PLANT COLLECTION FROM EAST NUSA TENGGARA EXPLORATION (EGON FOREST, MUTIS MOUNT, AND CAMPLONG PARK) AT PURWODADI BOTANIC GARDEN - Trimanto Trimanto (The East Java Biological Society, 2013)
Acclimatization is treatment to adapt the plants material from forest exploration. This activity determine the survival of plants material in nursery at Purwodadi Botanical Garden. Endemic and rare species from East Nusa Tenggara are expected to survive in the Purwodadi Botanic Garden plant collection. This research is aimed to observe acclimatization procces in Purwodadi Botanic Garden and to know the species of plant in East Nusa Tenggara which they can’t adapt in the Purwodadi Botanical Garden. The research was conducted at nursery unit with observational methods. The results show that 50% of 209 accession plants from East Nusa Tenggara can’t survive at Purwodadi Botanic Garden. It consists of 60 accession plants from Egon, 20 accession plants from Mutis, and 18 accession plants from Camplong.